Pengaruh Harga, Promosi dan Kualitas Produk terhadap Keputusan Pembelian pada PT Medan Jaya Pangan Mutu - Fransisco Eka Wijaya; Andy Susanto; Rosalinda Rosalinda; Mei Lan; Wirda Lilia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Writing this article aims to research and analyze the influence of price, promotion and product quality on purchasing decisions. Price is the value in money paid by consumers as a selling price of the product. Promotion is an activity in introducing products in a company with various benefits provided to customers. Product quality is the quality standard provided by the product that is expected by the customer. Issues are focused on the topics of price, promotion, product quality and purchasing decisions. In order to approach this problem, a theoretical reference for marketing management is used. The data were collected through interview methods, questionnaires and documentation studies and quantitatively analyzed. This study concluded that the variable price, promotion and product quality partially and simultaneously had a positive and significant effect on purchasing decisions at PT. Medan Jaya Food Quality with a coefficient of determination of 47%.